New results on the pulsating variable star GSC 4778:0324 - Gazeas, K. D.; Manimanis, V. N.; Niarchos, P. G. (Recent Advances in Astronomy and Astrophysics, 2006)
We report on the results of a series of photometric observations of the low-amplitude δ Scuti star GSC 4778:0324, in the course of a multi-site campaign aiming at monitoring V1162 Ori. The two dominant frequencies, found in the previous analyses based on the 2000-2002 data, are confirmed and their amplitudes are found to be stable on a time-scale of a few years.
Keywords: 97.10.Sj; 97.30.Dg; Low-amplitude blue variables; Pulsations oscillations and stellar seismology